A Comparative Study to Evaluate the Role of Organizational Ambidexterity on Firms Performance in Production and Service Sector - Yaghoob Mombeini; Mahmood Moradi; Mostafa Ebrahimpour (بهبود مدیریت, 2015)
With intensifying competition and accelerating changes speed, the organizational ambidexterity influenced firm performance and by the simultaneously efforts of organizations to exploit and explore the opportunities available in a dynamic environment is obtained. Organizational ambidexterity as is defined as the ability to align with business demands and at the same time being consistent with environmental changes. Exploration and exploitation are two dimensions of organizational ambidexterity. In this paper, the effect of organizational ambidexterity on the performance in the two manufacturing and services industry has been investigated. Furthermore, moderating role of environmental dynamics in the relationship between the organizational ambidexterity and performance has been addressed. Research data has been collected in the manufacturing sector from the Rasht Industrial Zone and in the services sector from the retail stores in Rasht. Data was collected through questionnaires and analyzed by structural equation modeling and partial least squares algorithm. Findings show that in the two manufacturing and services industry organizational ambidexterity dimensions influence on performance. Moreover, environmental dynamics cannot moderate the relationship between organizational ambidexterity and performance in manufacturing companies; however relationship between exploration and performance at retail companies was moderated by environmental dynamics.